Analisis Jalur Respons Hasil Kedelai (Glycine max (L.) Merr.) Varietas Unggul Nasional Terhadap Dua Cara Pemberian Kombinasi Pupuk Npk - Paul Benyamin Timotiwu; Yayuk Nurmiaty; Eko Pramono; Yosep Riando Kusuma (Politeknik Negeri Lampung., 2018)
Path analysis is one of the causal analysis and is an advanced analysis of correlation and regression studies. Path analysis is the development of correlation analysis that explains the closeness of the relationship between characters by way of outlining correlation coefficients into direct and indirect effects. This research was aimed to obtain information on the direct and indirect effects of agronomic characteristics on the production. This research uses Siti Maysaroh research data entitled â€œThe Effect of NPK Fertilizer on the Growth and Production of Four Soybean Varieties (Glycine max (L.) Merr)â€. The data that have been obtained will then be analyzed using path analysis method. Data is analyzed using Microsoft excel program. The results of this study show the difference between the two models, namely: on the way of fertilizer feeding two variables that directly affect the yield of soybean production is the weight of 100 grains, whereas on the way of giving a one-time fertilizer variable that directly affects the yield of soybean production is the number of pod.